Suppression of idiotype and generation of suppressor T cells with idiotype-conjugated thymocytes (The Rockefeller University Press, 1979)
Inoculation of A/J mice with syngeneic thymocytes conjugated with specifically purified A/J anti-phenylarsonate (anti-Ar) antibodies, selectively suppressed the subsequent synthesis of those anti-Ar antibodies which carry the major cross-reactive idiotype. High titers of anti-Ar antibodies were produced upon subsequent immunization but in most mice the idiotype was undetectable. Suppression similarly occurred in F1(A/J X BALB/c) and in C.AL-20 mice. Although some mice were suppressed when unconjugated antibody was injected, the suppressive effect was much more pronounced, particularly in the F1 and C.AL-20 recipients, when the antibody was coupled to thymocytes. The state of suppression could be adoptively transferred with T cells to mildly irradiated syngeneic recipients. A population enriched for B cells had little if any suppressive effect. There was no requirement for antigen in the generation of suppressors. Thymocytes conjugated with antibody did not induce idiotype-specific suppression in mice that had been recently challenged with antigen. Thymocytes from BALB/c and C57BL/10 mice were effective carriers for the anti-Ar antibodies, i.e., there was no evidence for H-2 restriction. The experiments demonstrate the feasibility of suppressing idiotype production and generating idiotype- specific suppressor T cells without the use of anti-idiotypic antibody or antigen.